The Effectiveness of the "Woo Sabak" Music Video Clip in Promoting Tourism. - Jamaludin, Mazlina; Sidhu, Parveen Sarjit; Jamal, Nor Ashikin (Social Sciences, Humanities and Education Journal (SHE Journal), 2024)
Woo SABAK," a music video clip, was created to promote agricultural tourism in Sabak Bernam. The video employs a dramatic theme to attract individuals and groups from urban areas to experience the serene agricultural landscapes and the tranquility of ‘Kampung life’. Social media platforms such as Instagram, TikTok, Facebook, WhatsApp, and Telegram were used to market Sabak Bernam as a desirable domestic destination, particularly targeting generations X, Y, and Alpha. The music video showcased local attractions like Laman Tebu Aidil, Lembah Bernam Restaurant, Ah Ma House, Bagan Nakhoda Omar Beach, Kerepek Tajuri Sdn Bhd, paddy fields, coconut plantations, fruit plantations, farms, and palm plantations. Music videos can effectively reach a broad audience and engage them, making it an ideal medium for this promotional effort. The objectives were to create a music video for the Sabak Bernam District Council, Selangor, and to assess its effectiveness as a promotional tool. The project's goal is to boost Sabak Bernam as a domestic agricultural tourism destination and aid the Sabak Bernam District Council in generating income for the local community. The Multimedia Cognitive Learning theory was applied to understand visitor behavior, and Design Thinking guided the development of the music video. Data from 134 questionnaires indicated that "WOO SABAK" successfully evoked emotions and fostered attachments, encouraging visits to Sabak Bernam.